Ciclo reproductivo de Creagrutus bolivari (Pisces: Characidae) en Venezuela - Ortaz, Mario (1997)
The reproductive cycle of Creagrutus bolivari females was studied in a tropical stream in northem Venezuela. Ovaries were classified inthree stages as a function of volume: "rest", "in maturation" and "mature". Body weight has· a higher correlation with ovarian weight than standard length. The slope of ovarian weight versus body weight increased with the stage of ovarian development. The main period for gonadal maturation and spawning was the dry season with a secondary period in the wet season. There was an increase in the female condition's factor at the beginning of the gonadal maturation. The condition factor decreases as the gonadal maduration process reaches the end of this cycle.